Communication Difficulties and Psychological Stress in Patients Receiving Mechanical Ventilation - Thapa, Dejina; Dahal, Anika; Singh, Rameshwari (Birat Journal of Health Sciences, 2019)
Introduction: Communication is fundamental for an individual to verbalize their feelings. Inability of the patient receiving mechanical ventilation to communicate the needs to the health care provider often leads to psychological stress. Objective: The objective of the study is to assess the communication difficulties and psychological stress in patients receiving mechanical ventilation. Methodology: A cross-sectional research design was used for the study. A total of 48 patient extubated within the preceding 72 hours, was taken as a sample by using a convenience sampling method. Data were collected by using a interview technique in patients from January–September 2018 from a 41- bedded ICU at Nobel Medical College Teaching Hospital. Data analysis was done by descriptive and inferential statistics. Results: Difficulty in communication was found where majority of the respondents (82.29%) rated general communication as extremely hard. The study further revealed that 100% of the respondents used hands for pointing and gesturing followed by shaking heads (65.38%), whisper (19.23%) and writing (11.53%). Sleeping and communication difficulty was the major problem 97.91% and 96.94% respectively. Majority of respondents (66.66%) scored Intensive Care Psychological Assessment Tool more than 7. In addition, there is significant association between the sex, total length of ventilation and prior experience with ICU (p= <0.05). Conclusion: Patient with mechanical ventilation experience a moderate to extreme level of psychological stress because they have difficulty in communicating their needs. Alternative communication methods should be developed, and health care provider should be aware about the communication difficulties, thereby reducing the stress caused by ineffective communication.